Advanced Manufacturing Technologies for Micro- And Nanosystems in Security and Defence 2018
DOI: 10.1117/12.2325547
|View full text |Cite
|
Sign up to set email alerts
|

Rational design of light-controlled microrobots

Abstract: Light Robotics is one of the newest progenies of the robotics family, bringing together advances in microfabrication and optical manipulation with intelligent control ideas from robotics and Fourier optics. The development of lightcontrollable microrobots capable of performing specific tasks at the microscale requires the ability to sculpt the two protagonists of the story: the light and the microrobots. Complex light sculpting for optical trapping has been in focus for over three decades, and its importance f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…For cylindrical micro-objects, experiments of trapping cylindrical viruses have shown that they tend to orient themselves with the axis of the optical trap [91]. To enable the optical trapping of micro-objects with a cylindrical shape, spherical features are added to the main body of the microrobots to enable effective trapping [92]. However, out-of-plane rotation is difficult to achieve.…”
Section: Sculpting Microrobots' Shapesmentioning
confidence: 99%
“…For cylindrical micro-objects, experiments of trapping cylindrical viruses have shown that they tend to orient themselves with the axis of the optical trap [91]. To enable the optical trapping of micro-objects with a cylindrical shape, spherical features are added to the main body of the microrobots to enable effective trapping [92]. However, out-of-plane rotation is difficult to achieve.…”
Section: Sculpting Microrobots' Shapesmentioning
confidence: 99%
“…An example is the work of by Aekbote et al., who functionalized SU‐8 microtools with streptavidin or IgG for cell attachment . We have recently developed a method for functionalizing microtools fabricated using the IP‐L 780 photoresist from Nanoscribe …”
Section: Strategies For Improving Optical Trapping In Biological Samplesmentioning
confidence: 99%
“…The other benefit is that they are low-powered and sometimes can be powered from distance without the need for an onboard active power source, e.g., light-powered microbots, magnetically actuated microbots, etc. Despite the existing technological challenges, untethered microbots have already shown tremendous potential for a wide range of applications, particularly in the biomedical field [6,7]. The developments in micro and nanofabrication have aided the evolution of miniature robotics with a variety of designs, control systems, and functions [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%